Predictions of the Distance Running Performances of Female Runners Using Different Tools - Lerebourg, Lucie; Guignard, Brice; L’Hermette, Maxime; Held, Eric; Coquart, Jérémy Bernard (International Journal of Sports Medicine, 2022)
This study examined the validity and compared the precision and accuracy of a distance-time linear model (DTLM), a power law and a nomogram to predict the distance running performances of female runners. Official rankings of French women (“senior” category: between 23 and 39 years old) for the 3000-m, 5000-m, and 10,000-m track-running events from 2005 to 2019 were examined. Performances of runners who competed in the three distances during the same year were noted (n=158). Mean values and standard deviation (SD) of actual performances were 11.28±1.33, 19.49±2.34 and 41.03±5.12 for the 3000-m, 5000-m, and 10,000-m respectively. Each performance was predicted from two other performances. Between the actual and predicted performances, only DTLM showed a difference (p<0.05). The magnitude of the differences in these predicted performances was small if not trivial. All predicted performances were significantly correlated with the actual ones, with a very high correlation coefficient (p<0.001; r>0.90), except for DTLM in the 3000-m, which showed a high correlation coefficient (p<0.001; r>0.895). Bias and 95% limits of agreement were acceptable because, whatever the method, they were≤–3.7±10.8% on the 3000-m, 1.4±4.3% on the 5000-m, and -2.5±7.4% on the 10,000-m. The study confirms the validity of the three methods to predict track-running performance and suggests that the most accurate and precise model was the nomogram followed by the power law, with the DTLM being the least accurate.
Keywords: estimation; modeling; time to exhaustion; validity; women athletes; track-and-field